A primary intraosseous cystic meningioma: Case report. (2017) - Caruso, Riccardo; Fini, Giuseppina; Pesce, Alessandro; Wierzbicki, Venceslao; Marrocco, Luigi; Piccione, Emanuele; Pasquini, Paola
Highlights: Intraosseous cystic meningioma is a very rare. There are no reports of similar cases in the last 30 years. Primary intraosseous meningioma is a subtype of primary extradural meningioma. Cystic meningioma is rare, 2–4% of all meningiomas. A meningioma with both characteristics is an exceptional occurrence. Abstract: Introduction: This is a very rare case of intraosseous cystic meningioma. There have been no reports of similar cases in the last 30 years. Presentation of case: A 62-year-old man, suffering from a swelling of the lateral wall of the left orbit was admitted to our hospital. MRI and CT scan showed a large intradiploic lesion involving the lateral wall of the orbit and the greater wing of the sphenoid. The lesion was cystic with a mural nodule. We operated the patient and removed completely the mural nodule and the fibrous wall of cyst. Histological examination showed that the mural nodule was a benign meningothelial meningioma. Discussion: Primary intraosseous meningiomas represent a subtype of primary extradural meningiomas; they comprise about 2% of all meningiomas and are therefore rare entities. Cystic meningiomas are rare, their incidence compared to all other types of meningiomas is of 2–4%. The presence of a meningioma with both characteristics: cystic and intraosseous, like in our case, is an exceptional occurrence. Conclusion: The surgical management of tumor was easy; its rarity means that the case is interesting.